2020
DOI: 10.1038/s41598-020-66421-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of uremic toxin–indoxyl sulfate in the rat model

Abstract: Chronic kidney disease (CKD) is deemed to be a worldwide health concern connected with neurological manifestations. The etiology of central nervous system (CNS) disorders in CKD is still not fully understood, however particular attention is currently being paid to the impact of accumulated toxins. Indoxyl sulfate (IS) is one of the most potent uremic toxins. The purpose of the present study was to assess IS concentrations in the cerebellum, brainstem, cortex, hypothalamus, and striatum with hippocampus of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 34 publications
1
42
0
1
Order By: Relevance
“…With respect to psychiatric disorders, IS has been associated with behavioral defects in preclinical models of anxiety and depression. The administration of IS into rodents’ drinking water results in increased concentrations of IS in the brain and increased blood–brain barrier permeability in an AHR-dependent manner, with accompanying increases in anxiety and cognitive deficits 31 , 32 . Monocolonization experiments with indole-producing Escherichia coli and isogenic mutants have shown that indole production by gut bacteria is sufficient to drive increases in anxiety- and depressive-like behavior in rats 33 .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to psychiatric disorders, IS has been associated with behavioral defects in preclinical models of anxiety and depression. The administration of IS into rodents’ drinking water results in increased concentrations of IS in the brain and increased blood–brain barrier permeability in an AHR-dependent manner, with accompanying increases in anxiety and cognitive deficits 31 , 32 . Monocolonization experiments with indole-producing Escherichia coli and isogenic mutants have shown that indole production by gut bacteria is sufficient to drive increases in anxiety- and depressive-like behavior in rats 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, IS has been associated with behavioral defects in preclinical models of anxiety and depression. The administration of IS into rodents’ drinking water results in increased concentrations of IS in the brain and increased blood-brain barrier permeability in an AHR-dependent manner, with accompanying increases in anxiety and cognitive deficits (27,28). Monocolonization experiments with indole-producing Escherichia coli and isogenic mutants have shown that indole production by gut bacteria is sufficient to drive increases in anxiety- and depressive-like behavior in rats (29).…”
Section: Introductionmentioning
confidence: 99%
“…Although current study revealed interesting findings, there were some limitations. In normal Albino Wistar rats, indoxyl sulfate (100 and 200 mg/kg) administration via drinking water for 28 days led to its increased accumulation in various brain regions and high dose of indoxyl sulfate (200 mg/kg) caused biochemical and behavioral alterations [ 56 ]. The same experimental conditions demonstrated higher plasma indoxyl sulfate concentrations in both two doses and the high dose treatment slightly impaired renal function [ 57 ].…”
Section: Discussionmentioning
confidence: 99%